Functional Loss After Meningitis—Evaluation of Vestibular Function in Patients With Postmeningitic Hearing Loss - West, Niels; Sass, Hjalte; Klokker, Mads; Cayé-Thomasen, Per (Frontiers in Neurology, 2020)
Introduction: The inner ear vestibular system is essential to balance function. Although hearing loss is well-described and quite common following meningitis, the literature evaluating vestibular function following meningitis is very limited. In particular, information on results of contemporary vestibular function tests, e.g., the video head impulse test (VHIT), is scarce. Using contemporary vestibular function tests, this study examines the vestibular function of patients with profound hearing loss (HL) after meningitis. Methods: Review of the literature and retrospective controlled study. Patients: Twenty-one consecutive patients with profound HL after meningitis (cochlear implant candidates) matched with 20 patients with profound HL of unknown etiology and examined during the period 2013–2018. Outcome Measure: Vestibular function loss, as evaluated with VHIT vestibulo-ocular reflex (VOR) gain, eye movement saccades, and cervical vestibular-evoked myogenic potentials (cVEMPs). The results of these tests were correlated to inner ear imaging findings (MRI/CT) and the level of hearing loss. Results: Mean VHIT gain was 0.48 in the meningitis group compared to 0.86 in the control group (p < 0.01). Saccades were present in 21 ears (62%) in the meningitis group compared to six ears (15%) among the controls (p < 0.01). cVEMP responses were present on five ears (18%) in the meningitis group and 25 ears (66%) in the control group (p < 0.01). Discussion: Postmeningitic hearing loss is associated with poor vestibular function, as evaluated by VHIT, saccades, and cVEMP. Loss of vestibular function correlates with the degree of hearing loss and inner ear imaging findings, although not in all cases. Vestibular function should be examined in patients surviving meningitis with hearing loss in order to individualize rehabilitation and improve balance outcome.